Long-Term Safety and Efficacy of CD19 Humanized Selective CAR-T Therapy in B-ALL Patients Who Have Previously Received Murine-Based CD19 CAR-T Therapy - Zhao, Yu; Zhang, Jianping; Yang, Junfang; Wu, Huantong; Chen, Yao; Li, Nannan; Liu, Zhongfeng; Wang, Xuan; Liu, Weihua; Zhang, Guangji; Zhou, Bin-Bing Stephen; Lu, Peihua; et al. (Frontiers in Oncology, 2022)
Murine-based CD19 CAR-T (CD19m CAR-T) therapy can lead to a relatively high CR rate when administered to B-ALL patients for the first time. However, the DOR is sub-optimal and a subset of patients even show primary resistance to CD19m CAR-T. To address these issues, we employed a humanized selective CD19CAR-T (CD19hs CAR-T) and evaluated the long-term safety and efficacy of treating 8 R/R B-ALL patients who had relapsed or failed to achieve CR following CD19m CAR-T infusion (Clinical trials’ number: ChiCTR1800014761 and ChiCTR1800017439). Of the 8 patients, 7 achieved CR on Day 30 after the 1st infusion of CD19hs CAR-T. The median CRS grade was 1 without significant neurotoxicity seen in any of the 8 patients. The median DOR was 11 months, significantly longer than the DOR following CD19mCAR-T infusions. Anti-CAR antibodies were induced in patients who had received prior CD19m CAR-T infusions but not in those following a single or repeated CD19hsCAR-T treatment, which probably had contributed to the sub-optimal DOR and/or failure of effective response in these patients. CD19hs CAR-T, in contrast, induced low immunogenicity compared with CD19m CAR-T, suggesting that a repeat dosing strategy might be feasible and efficacious for patients who have relapsed and/or show primary resistance to CD19m CAR-T therapy. In this clinical study, CD19hs CAR-T showed a significant clinical efficacy with mild side effect among patients with R/R B-ALL who had previously received CD19m CAR-T.